Mobile clinic users' opinions on health care service provision in the Muldersdrift area,Gauteng province - Tshabalala, Amme Mardulate (My University, 2006)
The use of the mobile clinics for rendering health care services in South Africa is part of the services rendered according to the Primary Health Care Service Package that was officially published in 2001. Mobile clinics have been found to be instrumental in rendering of health care especially in the rural and semi- rural areas. In the majority of these areas, the mobile clinic is the only source of health care provision at community level. Lack of well developed infrastructure and poor roads contribute to inaccessibility of health care services in rural and semi-rural areas. Health programmes are often of poor quality or offer incomplete services. Factors such as lack of knowledge of available health care services, satisfaction with the quality and range of services provided, and unavailability of the mobile clinic service when there is a health need, can result in the mobile health care clinic being less utilized. The purpose of the study was to address the following question: What are mobile clinic users’ opinions on health care service provision in the Muldersdrift area Gauteng Province? To answer the question three research objectives were formulated. These were to: describe the mobile clinic users’ level of service utilization, to assess their level of knowledge of available health care services and to determine their level of satisfaction with the services provided. To achieve the study objectives, an exploratory, descriptive survey was used as the research design. Three sampling techniques were used in this study. Cluster sampling was used for developing sampling framework for the 35 mobile points. Stratified sampling used to stratification of the mobile points. A non- probability convenience sampling was then used for final selection of the nine mobile clinic points and for selection of a sample size of 94 mobile clinic users’ to be included in the study. Data were analysed using the Statistical Package 7.0. The results show that the mobile clinic service was optimally utilized, 59% had used the service more than thrice within a period of six months. The majority of participants (89.3%) had knowledge of all the services being offered on the mobile clinic. Very few respondents (19.5%) were aware of the availability of HIV and AIDS counseling and testing on the mobile clinic. All most all the respondents (98.9%) were satisfied the range of services offered on the mobile clinic. Almost half (48.9%) were not satisfied with the service being offered once a month, (4.4%) with the attitude of the staff, (5.3%) with treatment of common ailments and (2%) said the mobile clinic service was bad.
Student Number : 0008922X - MPH research report - Faculty of Health Sciences
Keywords: mobile clinics; health care services; South Africa; rural areas; semi- rural areas; infrastructure; poor roads; incomplete services; Muldersdrift area; Gauteng